Evaluating Methodology in International Studies. - Harvey, Frank P.; Brecher, Michael (University of Michigan Press, 2009)
Evaluating Methodology in International Studies offers a unique collection of original essays by world-renowned political scientists. The essays address the state of the discipline in regard to the methodology of researching global politics, focusing in particular on formal modeling, quantitative methods, and qualitative approaches in International Studies. The authors reflect on the strengths and weaknesses of current methodology and suggest ways to advance theory and research in International Studies. This volume is essential reading for methods courses and will be of interest to scholars and students alike. See table of contents and excerpts. Frank P. Harvey is Professor of Political Science and Director of the Centre for Foreign Policy Studies at Dalhousie University. Michael Brecher is the R.B. Angus Professor of Political Science at McGill University and past president of the International Studies Association. Millennial Reflections on International Studies This volume is part of the Millennial Reflections on International Studies project in which forty-five prominent scholars engage in self-critical, state-of-the-art reflection on international studies to stimulate debates about successes and failures and to address the larger questions of progress in the discipline. Other paperbacks from this project: Realism and Institutionalism in International Studies Conflict, Security, Foreign Policy, and International Political Economy: Past Paths and Future Directions in International Studies Critical Perspectives in International Studies The full collection of essays is available in the handbook Millennial Reflections on International Studies.